Impact of Job Stress on Consumer Satisfaction with Role of Mediating Variables (Employee Satisfaction and Employee Performance): A Study of Punjab Emergency Service (Rescue 1122) Sahiwal, Pakistan - Sabir, Raja Irfan; Akhtar, Naeem; Zakir, Usman; Nadeem, Iram; Rehman, Asad Ur (Journal of Asian Business Strategy, 2014)
Rescue 1122 is playing a vital role in rescue services in Punjab. Rescue services basically upon employee’s efficiency. Low wages, extra working hours, fake and irrelevant phone calls are the causes of stress on employees and resultantly employee’s satisfaction impact on customer’s satisfaction. This study will investigate the impact of stress on employees and its impact on customer’s satisfaction and dissatisfaction. The researcher will use explanatory research and describe the phenomena of employees and customer’s satisfaction and dissatisfaction. The study will use the entire population of Sahiwal Region and by using stratified sampling method. In a sample of 600 people, 300 employees and 300 customers of Rescue 1122 will be used. Researcher will use the survey method and an adopted questionnaire for collection of data. A Software SPSS will be used for data analysis. Findings of this research will be used for Rescue 1122 employee’s and customer awareness.